Resolving the Conflict of Interests Issue within the Laws Concerning the Political Matters: Deliberative Democracy or Empowering Dewan Perwakilan Daerah? - Taqwa, Muhamad Dzadit; Sirait, Melinda Yunita Lasmaida; Alfarizy, Ahmad (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2023)
This study examines whether the concept of deliberative democracy could offer a viable solution to the issues surrounding laws on political matters, commonly referred to as Paket Undang-Undang Politik in Indonesia. These laws, including general election regulations, have become problematic due to their close association with the drafters. Over the past two decades, presidents and the majority in the House of Representatives have formed coalitions to maintain government stability. However, this success has had a detrimental impact on the system of checks and balances during the drafting of these laws. While the Constitutional Court could potentially intervene by reviewing these laws, it has often not addressed the conflict of interest issues arising from open legal policies, especially in cases related to reviewing election laws. This paper addresses this issue by proposing a solution integrated into the drafting process to mitigate conflicts of interest in political matters legislation. The proposed approach involves incorporating an additional institution in the drafting process not directly influenced by political interests. In other countries, similar issues are tackled through practical implementations of deliberative democracy, which directly involves citizens as the decisive factor, using methods such as citizen assemblies and deliberative polling. We suggest empowering the Regional Representatives Council could offer a more practical solution to this issue.DOI: https://doi.org/10.22304/pjih.v10n3.a2